Religious Community Movement Online: Tracking History And Transformation Of Islamic Dakwah in Indonesia - Wely Dozan; Hopizal Wadi (IAIN Kendari, 2021)
This article generally examines online religious communities; more specifically, this article reviews religious communities in Indonesia with the object of study by the United Muslim community. Muslim United is one of the online religious communities in Indonesia. This community has various kinds of programs, including conducting da'wah activities through social media and a massive alms program at dawn which is carried out to assist in distributing fruits to class communities lewd. This article explains specifically about the united Muslim community that exists on social media. The method used in this article is ethnography, a method that collects data through the Muslim United Instagram account and also searches for other data from the YouTube, Twitter accounts that are specific about activities in the Muslim United community. This study indicates that the Muslim community is united in opening up hijrah spaces for young people and carrying out religious, social movements without any politics.